A Review of Recent Research on the History of Universities and Students in France - Moulinier, Pierre (CIAN-Revista de Historia de las Universidades, 2017)
In France, the active community of researchers studying education and young people usually focus their research on children and adolescents while research on education is limited to elementary schooling. Yet research on the history of French universities and the student population does exist. The higher education reform introduced after the 1968 student revolt swept away the early 19th century Napoleonic model of a university based on the primacy of specialized faculties (the humanities, science, medicine, law, pharmacy) but endowed with little power, a transformation that inspired some important research on the general history of French universities and also on the history of certain provincial universities. Numerous monographs describe the new, post-1968 establishments or mark the anniversary of an older, even medieval institution. Some promising research has also been undertaken on the history of students, a relatively new topic and one that will benefit from the creativity of dedicated research organizations.
Keywords: history of faculties; history of universities; history of students; students’ associations; the higher education reform